New species of Vetuprostomis from mid-Cretaceous amber of northern Myanmar (Coleoptera: Tenebrionoidea: Prostomidae) - Li, Yan-Da; Hsiao, Yun; Huang, Di-Ying; Cai, Chen-Yang (Zootaxa, 2022)
Two new species of the prostomid genus Vetuprostomis Engel & Grimaldi (Coleoptera: Tenebrionoidea: Prostomidae), V. angularis Li & Cai sp. nov. and V. gaoi Li & Cai sp. nov., are described from the mid-Cretaceous Burmese amber. Vetuprostomis is suggested to be more closely related to extant Dryocora Pascoe distributed in Australia and New Zealand, rather than the widespread genus Prostomis Latreille. A key to prostomid genera, as well as species in genus Vetuprostomis, is provided.